Effect of hr development on employee performance where work environment and work communication as moderating variables - Palupi Martasari; Sapto Supriyanto; Enik Rahayu (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The purpose of this study is to analyze and explain of human resource development on employee performance where the work environment and work communication as moderating variables (study at the Regional Secretariat of Demak Regency). Research data was obtained through secondary data documentation and questionnaires with sample used in the  research was 106 respondents. The results of the study are expected to provide useful information for employees and the Regional Secretariat of Demak Regency. The data obtained were processed using  descriptive analysis and quantitative statistical analysis.  This  study uses moderated regression with the interaction method or often referred to as Moderated Regression Analysis (MRA), but before the test is carried out, the validity and reliability tests are carried out first and hypothesis testing. The results of the analysis show that human resource development has a positive and significant influence on employee performance at the Regional Secretariat of Demak Regency. The work environment and work communication moderated positively and significantly the influence of human resource development on employee performance at the Regional Secretariat of Demak Regency.